Pollution as one of the determinants of income in Malaysia: comparison between single and simultaneous equation estimators of an EKC / Halimahton Borhan and Elsadig Musa Ahmed - Borhan, Halimahton; Musa Ahmed, Elsadig (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
This study aims to examine the relationship between economic growth and different indicators of air and water pollution in Malaysia. Air pollution indicators were assessed on a number of measures: carbon monoxide, sulphur dioxide (SO2), nitrogen dioxide, ozone and particulate matter (PM 10); while water pollution indicators is evaluated based on a number of measures: biochemical oxygen demand, cadmium and arsenic. The income level per capita gross domestic product per capita were measured from the year 1996 to 2006 quarterly. Being different from the study by Hung and Shaw (2004) and Shen (2006), this study estimates population density as an endogenous variable. It formulates a four-equation simultaneous model for empirical research. Hausman test is utilized to test for exogeneity and the two-stages least squares method is used to estimate the simultaneity model. The Environmental Kuznets Curve (EKC) hypothesis is supported in the cases of SO2 and PM 10, and there are several differences found between single polynomial equation estimators commonly used in EKC literatures and simultaneous equation estimators.